TRADITIONAL AND DOVETAIL CORE JOINTS IN ADVANCED COMPOSITE SANDWICH STRUCTURES: A MULTI-METHOD ASSESSMENT - (:unkn) unknown (My University, 2025)
Composite sandwich panels are extensively utilized in aerospace, marine, and civil infrastructure due to their exceptional stiffness-to-weight and strength-to-weight characteristics. Honeycomb sandwich structures, in particular, are favored for their high strength-to-weight ratio, energy absorption capability, and excellent thermal and acoustic insulation. However, the fabrication and repair of large-scale panels often require core splicing, which introduces discontinuities that can compromise shear transfer, reduce stiffness, and trigger premature failure. This dissertation presents a comprehensive investigation into the structural implications of honeycomb core splicing, with a focus on the performance degradation associated with traditional splice and splice gaps. A multidisciplinary research approach was employed combining experimental testing, nondestructive evaluation, and advanced numerical simulations to assess the effects of various splice configurations on mechanical performance and structural integrity. Experimental results showed that unbonded splice regions reduced load capacity by up to 80%, while adhesive-filled splices improved performance and failure predictability, though they did not fully restore the strength of intact specimens. A novel dovetail splice design was introduced and demonstrated the ability to restore, and in some cases exceed, the mechanical performance of intact panels. Finite element models supported these findings, showing that optimized dovetail geometries reduced stress concentrations and delayed failure onset, offering a scalable and manufacturable solution for high-performance applications. The study also investigated torsional stiffness degradation using the Impulse Excitation Technique (IET), a sensitive and scalable nondestructive method. IET proved effective in detecting stiffness losses and distinguishing between localized and global damage modes. Additionally, a simulation case study using ESAComp modeling the Boeing 787 passenger door highlighted the effectiveness of incorporating experimentally derived knockdown factors to model core degradation. Results confirmed that core continuity is critical for structural reliability, and that splice configuration significantly influences stiffness, strength, failure behavior, and damage location. Based on these findings, it is recommended that core splices be avoided in high-shear regions such as near supports. This research advances the understanding of core-spliced composite sandwich structures and offers practical strategies for their design, evaluation, and structural health monitoring, contributing to safer and more durable high-performance composite systems.
Keywords: Civil engineering; Materials Science; Mechanics; Composite Sandiwch Structures; Core Joints / Core Splicing; Dovetail; EIT; FEA; Shear Behaviour